Balancing Wallet And Planet: The Financial, and Environmental Drivers of Eco-Friendly Coffee Purchase Intention - Suarsa, Abin; Kaswoto, Junet; Hakim, Cikita Berlian; Waeno, Mahamadaree; Zakaria, Muhammad Firdaus Bin; Munzir, Munzir (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
This study examines the effects of financial literacy, knowledge awareness, price affordability, and trust in eco-labels on the intention to buy eco-friendly coffee in Indonesia. Using an explanatory quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) and data from 300 respondents, the findings reveal that price affordability significantly affects green purchase intention, while financial literacy has no direct effect. Knowledge awareness enhances trust in eco-labels, which mediates the relationship between knowledge awareness and green purchase intention. Moreover, price affordability moderates the effect of knowledge awareness on green purchase intention. These results highlight the importance of balancing financial considerations and ecological awareness to promote sustainable coffee consumption.